Simultaneously ultrafast and robust two-dimensional flash memory devices based on phase-engineered edge contacts - Yu, Jun; Wang, Han; Zhuge, Fuwei; Chen, Zirui; Hu, Man; Xu, Xiang; He, Yuhui; Ma, Ying; Miao, Xiangshui; Zhai, Tianyou (Nature communications, 2023)
As the prevailing non-volatile memory (NVM), flash memory offers mass data storage at high integration density and low cost. However, due to the ‘speed-retention-endurance’ dilemma, their typical speed is limited to ~microseconds to milliseconds for program and erase operations, restricting their application in scenarios with high-speed data throughput. Here, by adopting metallic 1T-Li x MoS 2 as edge contact, we show that ultrafast (10–100 ns) and robust (endurance>10 6 cycles, retention>10 years) memory operation can be simultaneously achieved in a two-dimensional van der Waals heterostructure flash memory with 2H-MoS 2 as semiconductor channel. We attribute the superior performance to the gate tunable Schottky barrier at the edge contact, which can facilitate hot carrier injection to the semiconductor channel and subsequent tunneling when compared to a conventional top contact with high density of defects at the metal interface. Our results suggest that contact engineering can become a strategy to further improve the performance of 2D flash memory devices and meet the increasing demands of high speed and reliable data storage. The speed-retention-endurance trade-off usually limits the performance of flash memory devices. Here, the authors report the realization of van der Waals flash memory cells based on 2H-MoS 2 semiconducting channels with phase-engineered 1T-Li x MoS 2 edge contacts, showing program/erasing speed of ~10/100 ns, endurance of >10 6 cycles and expected retention lifetime of >10 years.